The important role of community nurses post pandemic covid-19 - Akbar, M Agung (Science Center Group, 2024)
The COVID-19 pandemic has highlighted the pivotal role of community nurses in public health, particularly within local communities. This article examines the expanded responsibilities of community nurses in the post-pandemic era, focusing on their essential contributions to healthcare delivery, mental health support, health education, and chronic disease management. With an increased demand for long-term health monitoring for COVID-19 survivors, community nurses have become integral in guiding patients through rehabilitation and managing persistent symptoms. Their role in health education and prevention has also grown, as they educate communities on hygiene practices and vaccination to prevent future outbreaks. Additionally, community nurses provide critical mental health support and assist in the management of chronic conditions that have intensified post-pandemic. The article concludes by emphasizing the importance of supporting and investing in community nurses to strengthen public health infrastructure and prepare for future health crises.